Earthquake Education Through the Use of Documentary Movies - Navakanesh, Batmanathan; Shah, Afroz Ahmad; Prasanna, M. V. (Frontiers in Earth Science, 2019)
Unscientific, false, inaccurate and/or exaggerated reporting about anything in media or other platforms is a serious concern that needs a solution. This is particularly important when reporting about disasters (e.g. earthquakes). The lack of authentic scientific input into science news reporting may lead to news disasters, which may prove to be much more critical and dangerous than say -earthquake disasters. Therefore, this paper explores such a problem in a portion of NW Borneo and offers solution to improve the existing norms on the earthquake science, education and awareness programs in SE Asia. The explored field location is Sabah, Malaysia, which is targeted to map the level of earthquake science education and awareness of local people, and to examine the co-seismic deformation associated with the 5th June, 2015 earthquake. This event has surprised the local communities because the region is geographically located away from the active tectonic plate boundaries, and has traditionally been considered a low earthquake risk region. This is in contrast to the existence of high earthquake hazard and risk regions in the neighboring Indonesia and the Philippines. Therefore, not surprisingly, the residents of Borneo where puzzled, surprised and worried when a medium magnitude earthquake occurred and caused significant loss of life and property. The lack of scientific education on the causes, and remedies of earthquake hazards in most of the South and Southeast Asian regions is a reality, which needs a real solution. Therefore, through this work a small initiative has been started in Sabah, Malaysia where stories from the earthquake victims were recorded after the devastation caused by the June 2015 earthquake. Their real time experiences were blended with the updated scientific data on the occurrence of earthquakes in Borneo, which are mostly gathered from previously published works and the work presented here. The entire work is converted into a small documentary movie that highlights the causes of earthquake and how it impacts human life.